2010
DOI: 10.4049/jimmunol.1002273
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Thymic NK Cells Develop Independently from T Cell Precursors

Abstract: Although NK cells in the mouse are thought to develop in the bone marrow, a small population of NK cells in the thymus has been shown to derive from a GATA3-dependent pathway. Characteristically, thymic NK cells express CD127 and few Ly49 molecules and lack CD11b. Because these NK cells develop in the thymus, the question of their relationship to the T cell lineage has been raised. Using several different mouse models, we find that unlike T cells, thymic NK cells are not the progeny of Rorc-expressing progenit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 27 publications
(40 reference statements)
4
37
0
1
Order By: Relevance
“…Furthermore, our choice to use Rag1 Ϫ/Ϫ mice was further supported by a recent publication indicating that thymic NK cells are not derived from thymocytes having undergone antigen receptor rearrangement. 25 While earlier in vitro studies showed that NK1.1 ϩ cells are generated from CD117 ϩ cells within the DN1 thymic population, 17 our studies indicate that in Rag1 Ϫ/Ϫ mice, there is a DN1 CD122 ϩ NK1.1 ϩ population that may have skewed our results if not sorted out. Future experiments to enrich for the CD117 ϩ population may be informative but additional markers will still be needed to markedly increase precursor frequency.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Furthermore, our choice to use Rag1 Ϫ/Ϫ mice was further supported by a recent publication indicating that thymic NK cells are not derived from thymocytes having undergone antigen receptor rearrangement. 25 While earlier in vitro studies showed that NK1.1 ϩ cells are generated from CD117 ϩ cells within the DN1 thymic population, 17 our studies indicate that in Rag1 Ϫ/Ϫ mice, there is a DN1 CD122 ϩ NK1.1 ϩ population that may have skewed our results if not sorted out. Future experiments to enrich for the CD117 ϩ population may be informative but additional markers will still be needed to markedly increase precursor frequency.…”
Section: Discussionmentioning
confidence: 65%
“…16,17 Recent in vivo experiments further showed that thymic NK cells do not express Rag2 and do not rearrange TCR␥ locus, suggesting that thymic NK cells are not derived from a committed T cell progenitor. 25 In either case, whether these NK1.1 ϩ cells were functional is unknown. Therefore, prior studies provide a framework for considering NK cell differentiation, but further analysis is required to understand the acquisition of markers during development and the relationship of DN1 cells to thymic and conventional NK cells.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that Notch signaling is essential for T cell commitment in ETPs (32,48). In contrast, Notch signaling is dispensable for thymic NK cell differentiation in mice (49,50 (32,48). Conversely, Notch2 can promote early T cell commitment of Notch1-deficient HSCs in coculture with OP9-DL1 stroma cells and possibly in vivo in the spleen after BM transplantation (32).…”
Section: Discussionmentioning
confidence: 99%
“…Although Id2 is essential for optimal development of NK cells, this molecule plays an important role at a later developmental stage in the transition of pre-NK to immature NK cells [7,21,59]. Of note, the development of mouse thymic NK cells is dependent on IL-15, IL-7, and Gata-3 [60]. In mice, there is a population of thymic NK cells which are identical to human CD56 hi CD16 dim/À NK cells and express CD127, high levels of Table 1 Characteristics of CD markers, localization and signature cytokine of ILC subsets.…”
Section: Ilc Developmentmentioning
confidence: 98%